PERTANGGUNGJAWABAN PERDATA FRANCHISOR ATAS KESALAHAN PEMBERIAN WARALABA KEPADA FRANCHISEE - Try Mulyaningsih (2023)
One way to cooperate in the field of trade is to use a franchise system. One form of illegal act in franchising is the franchisor making a mistake in granting a franchise and then entering into a franchise agreement and resulting in a loss. The objective of this study is to determine the form of the illegal acts of the franchisor against the franchisee in the process of granting a franchise and to determine the form of civil liability of the franchisor that made a mistake in granting a franchise to the franchisee. This study uses a normative legal research method with a statutory approach, a conceptual approach and a case approach. The data source used is secondary data, which consists of primary, secondary and tertiary legal materials. The conclusion of this study is that the illegal act of the franchisor in the process of granting a franchise is that the franchisor does not have a Franchise Registration Certificate, but enters into a franchise agreement with the franchisee. The form of liability for franchisors who make mistakes in granting franchises to franchisees is compensation. Government Regulation Number 42 of 2007 and Ministry of Commerce Regulation Number 71 of 2019 do not regulate the principle of responsibility that is applied. The problem with the franchise agreement in terms of franchising is that there are legal loopholes that can lead to illegal acts. Therefore, there is a need for a Franchise Law.